Existence of the Mild Solutions for Impulsive Fractional Equations with Infinite Delay. (15th October 2011) - Dabas, Jaydev; Chauhan, Archana; Kumar, Mukesh
Abstract : This paper is concerned with the existence and uniqueness of a mild solution of a semilinear fractional-order functional evolution differential equation with the infinite delay and impulsive effects. The existence and uniqueness of a mild solution is established using a solution operator and the classical fixed-point theorems.